Novel brain permeant mTORC1/2 inhibitors are as efficacious as rapamycin or everolimus in mouse models of acquired partial epilepsy and tuberous sclerosis complex. (1st December 2020) - Theilmann, Wiebke; Gericke, Birthe; Schidlitzki, Alina; Muneeb Anjum, Syed Muhammad; Borsdorf, Saskia; Harries, Timon; Roberds, Steven L.; Aguiar, Dean J.; Brunner, Daniela; Leiser, Steven C.; Song, Dekun; Fabbro, Doriano; et al.
Abstract: Mechanistic target of rapamycin (mTOR) regulates cell proliferation, growth and survival, and is activated in cancer and neurological disorders, including epilepsy. The rapamycin derivative ("rapalog") everolimus, which allosterically inhibits the mTOR pathway, is approved for the treatment of partial epilepsy with spontaneous recurrent seizures (SRS) in individuals with tuberous sclerosis complex (TSC). In contrast to the efficacy in TSC, the efficacy of rapalogs on SRS in other types of epilepsy is equivocal. Furthermore, rapalogs only poorly penetrate into the brain and are associated with peripheral adverse effects, which may compromise their therapeutic efficacy. Here we compare the antiseizure efficacy of two novel, brain-permeable ATP-competitive and selective mTORC1/2 inhibitors, PQR620 and PQR626, and the selective dual pan-PI3K/mTORC1/2 inhibitor PQR530 in two mouse models of chronic epilepsy with SRS, the intrahippocampal kainate (IHK) mouse model of acquired temporal lobe epilepsy and Tsc1 GFAP CKO mice, a well-characterized mouse model of epilepsy in TSC. During prolonged treatment of IHK mice with rapamycin, everolimus, PQR620, PQR626, or PQR530; only PQR620 exerted a transient antiseizure effect on SRS, at well tolerated doses whereas the other compounds were ineffective. In contrast, all of the examined compounds markedly suppressed SRS in Tsc1 GFAP CKO mice during chronic treatment at well tolerated doses. Thus, against our expectation, no clear differences in antiseizure efficacy were found across the three classes of mTOR inhibitors examined in mouse models of genetic and acquired epilepsies. The main advantage of the novel 1, 3, 5-triazine derivatives is their excellent tolerability compared to rapalogs, which would favor their development as new therapies for TORopathies such as TSC. Highlights: The mTOR inhibitor everolimus is used for treatment of partial epilepsy in patients with TSC Everolimus and other rapalogs may also be useful for other types of epilepsy, but adverse effects limit their use Here we compared the efficacy of rapalogs and novel mTOR inhibitors in two mouse models All mTOR inhibitors suppressed seizures in a TSC mouse model but were ineffective in a model of acquired epilepsy The main advantage of the novel compounds is their excellent tolerability compared to rapalog